CASE REPORTFistulization of hydatid mediastinal cyst to the anterior thoracic wall: case report - Sevinc, Serpil; Samancıiar, Ozgur; Ozturk, Taner; Unsal, Saban; Kaya, Seyda Ors (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Echinococcosis/hydatidosis is a frequent parasitic and zoonotic disease in the population engaged with agriculture and stockbreeding. It is seen most frequently in the liver and lung in adults. Mediastinal location of the disease is very rare. In this study we aimed to present a 31-year-old man having hydatid disease in the anterior mediastinum fistulated to the skin in the right subclavicular region, together with the literature. The patient was operated on through a partial sternotomy incision, and excision of the cyst and the fistula was performed